Characterization of Autonomous Work in a Chilean English Pedagogy Program: Teachers’ and Freshmen’s Perspectives - Roxanna Correa-Pérez; María Gabriela Sanhueza-Jara (Revista Electrónica Educare)
Autonomy in language learning is recognized as a basic skill language learners need to develop. This study describes the autonomous work activities university students carry out in a first-semester course of an English teaching program, and the amount of time they invest in each of these activities. Moreover, it describes the teachers’ perspective on students’ autonomous work. It is a descriptive mixed study with an exploratory scope. The study considers data generated through the application of a questionnaire and an in-depth interview to 48 freshmen from an English Pedagogy Program, as well as a questionnaire and a focus group applied to eight English teachers from the same program. The qualitative data were analyzed through content analysis method; and the quantitative data, through a frequency method of analysis. The analysis reveals that there is an imbalance between the time teachers estimate students devote to autonomous work and the real time students declare to invest in it. In relation to students autonomous work activities, it can be concluded that they concentrate on activities which are less stressful and the ones they do not need to interact with teachers. This study provides empiric information that could be useful to design courses that consider autonomous work.